2023
DOI: 10.1172/jci.insight.161229
|View full text |Cite
|
Sign up to set email alerts
|

Targeting activin receptor–like kinase 7 ameliorates adiposity and associated metabolic disorders

Abstract: Activin receptor-like kinase 7 (ALK7) is a type I receptor in the transforming growth factor-β superfamily preferentially expressed in adipose tissue and associated with lipid metabolism.Inactivation of ALK7 signaling in mice results in increased lipolysis and resistance to both genetic and diet-induced obesity. Human genetic studies have recently revealed an association between ALK7 variants and both reduced waist-to-hip ratios and resistance to development of diabetes. The present study found that treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
3
13
0
Order By: Relevance
“…In fact, we found no alternations in glucose-stimulated insulin secretion from isolated islets of genetically ALK7deficient mice [12] or mice treated with ALK7 neutralizing antibody [13]. Furthermore, the protein and mRNA levels of ALK7 in islets were negligible compared with those in WAT, which is consistent with the previous findings that ALK7 transcripts are predominantly expressed in adipose tissues compared with other tissues in both mice and humans [14,15].…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…In fact, we found no alternations in glucose-stimulated insulin secretion from isolated islets of genetically ALK7deficient mice [12] or mice treated with ALK7 neutralizing antibody [13]. Furthermore, the protein and mRNA levels of ALK7 in islets were negligible compared with those in WAT, which is consistent with the previous findings that ALK7 transcripts are predominantly expressed in adipose tissues compared with other tissues in both mice and humans [14,15].…”
Section: Introductionsupporting
confidence: 91%
“…In any case, it should be kept in mind that this BATspecific ALK7-knockout mouse may display phenotypes indirectly or partly reflecting ALK7 deficiency in WAT, because UCP1 is expressed in 'beige' or 'brite' adipocytes in WAT [28], especially after fasting or cold exposure. In fact, we found that UCP1 is induced in WAT of mice treated with ALK7 neutralizing antibody [13].…”
Section: Fat-specific Alk7-knockout Micementioning
confidence: 74%
See 3 more Smart Citations